The Influence of Integrated Management Neonatal and Childhood Illness Training on Knowledge, Attitude, Motivation and Compliance of Midwife Neonatal Visit - Timorini, Yuda Ayu; Handayani, Oktia Woro Kasmini; Rahayu, Rr. Sri Ratna (Public Health Perspective Journal, 2020)
Neonatal mortality rate (NMR) in Tegal Regency from 2015-2017 has contributed significantly to infant mortality, which is 70-81% and is ranked the 3rd largest in neonatal deaths in Central Java Province. One reason is the level of knowledge and handling of officers in the steps of Integrated Management of Neonatal and Childhood Illness (IMNCI) in neonatal visits is still low. This study aims to simultaneously analyze the influence of IMNCI training on midwives' knowledge, attitudes, motivations and compliance of neonatal visit in Tegal Regency. This study used a quasi-experimental research design with a pretest-posttest design with a control group design, with a sample of 54 respondents namely 27 midwives as a control group and 27 midwives as an intervention group. The results showed a simultaneous difference in the intervention group between IMNCI training on knowledge, attitudes, motivation and compliance of midwife neonatal visit in Tegal Regency where the results of the Manova analysis showed a significance value of less than 0.05 (p = 0,000). The results of this study can be taken into consideration in taking the policy of the IMNCI program as one of the actions to increase the achievement of neonatal visits with IMNCI approach in an effort to reduce morbidity and infant mortality, especially in neonatal period.Ã‚Â